Continuance intention of mobile banking services among generation Y / Tham Jia Hui, Muhammad Asyraf Hasim and Muhammad Ammar Shafi - Tham, Jia Hui; Hasim, Muhammad Asyraf; Shafi, Muhammad Ammar (UiTM Cawangan Negeri Sembilan, 2023)
In recent years, especially during the COVID-19 pandemic, more people have been using mobile banking services. Mobile banking will grow in the long run as long as people keep using it. Thus, the objective of this study was to investigate what factors affect Generation Y (Gen-Y) customers’ continuance intention to utilize mobile banking services. These factors include perceived usefulness, perceived risk, and security. The researcher also evaluated their level of intention to use these services. This study used quantitative methods by distributing online questionnaires in Google form to Gen-Y users who used mobile banking services in Johor, Malaysia. Respondents are Gen-Y born between 1981 and 1996 who are 26 and 41 years old in year 2022. Data were computed using Statistical Packages for Social Science software. Multiple regression analyses were done to determine how the dependent and independent variables were related. The results showed that perceived usefulness, security, and perceived risk have a positive relationship with continuance intention. There was a high level of Gen- Y intention to keep using mobile banking services in the future. This study could give financial institutions valuable ideas for improving and developing their services.